"You can't stop the waves, but you can learn how to surf": Realized mindfulness in practice for parenting women in recovery. (May 2022) - Gannon, Meghan; Mackenzie, Michael; Short, Vanessa; Reid, Lindsay; Hand, Dennis; Abatemarco, Diane
Abstract: Background: The opioid crisis is a public health issue, contributing to poor maternal child health outcomes. A Mindfulness Based Parenting (MBP) intervention, part of the "Practicing Safety Mindfulness Project for Mothers in Drug Treatment" (PSMDT) study, was previously tested as an intervention to mitigate stress and improve parenting domains in a sample of parenting women in treatment for substance use disorder. Methods: Qualitative data from focus groups and Mindfulness Based Parenting group teacher process notes were analyzed to understand how participants applied mindfulness to their daily lives and how mindfulness affected their relationship with their child(ren). Results: Thematic analyses revealed three overarching major themes: 1) Supportive Tools to Assist with Bringing Mindfulness into Daily Living; 2) Application of Embodied Tenets of Mindfulness to Perspective and Behavior and 3) Mindfulness Based Parenting and Recovery. Transference of mindfulness skills to parenting was evident through both focus group and process note data, illustrating how mindfulness behaviors were incorporated into family life. Data also revealed how tools utilized in the MBP intervention affected participant recovery. Conclusions: MBP intervention shows utility in improving parenting and recovery domains. Data from this study will inform future iterations of this intervention and this contextual analysis can be used to inform other recovery programs looking to utilize mindfulness as an adjunctive treatment. Highlights: Mindfulness Based Parenting shows utility in pregnant and parenting women with Opioid Use Disorder, in relation to parenting and recovery domains. Mindfulness skills were transferred from mother to child, illustrating how mindfulness can be incorporated into interventions addressing the mother child dyad. Mindfulness Based Parenting may be a feasible intervention to address the guilt associated with maternal substance use.